A Semiotic Analysis of Verbal and Non-Verbal Signs in Harassment Awareness Posters - Ni Ketut Krisna Andriani; I Made Yogi Marantika (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
This study aims to identify and interpret the verbal and non-verbal signs used in harassment awareness posters. This study employed descriptive qualitative approach, as the analysis required the use of descriptive sentences. There are three theories used in this study detailing as follows; identifying the verbal and visual signs found on the selected harassment posters based on semiotics theory by Saussure (1983), analyzing the meanings of the signs in line with the theory of meaning by Barthes (1977) and supported by theory of color developed by Cerrato (2012). The result of this study shows that there are 5 verbal and 17 non-verbal signs found from those chosen harassment posters. In addition to visual and verbal signs, the posters conveyed both denotative and connotative meanings. Furthermore, analyzing the connotative meaning also involved examining the use of color terms, messages of warning and prevention in order to avoid harassment, while, the colors in the posters were deliberately used to reinforce the visual signs and deliver the message more effectively